Dataset for Tier 1 and 2 methodologies for estimating intake and enteric methane emission factors from smallholder cattle systems in Africa: A case study from Ethiopia - Balcha, Endale; Ndung'u, Phyllis Wanjungu; Getahun, Daniel; Graham, Michael; Marquardt, Svenja; Mulat, Daniel Girma; Merbold, Lutz; Wilkes, Andreas; Worku, Tigist; Gakige, Jesse; Arndt, Claudia (International Livestock Research Institute, 2024)
These datasets include enteric methane emission factors derived using the Common Commonwealth Scientific and Industrial Research Organization (‘CSIRO’) and Intergovernmental Panel on Climate Change (IPCC) Tier 2 methods. The activity data collected includes the live weight (LW) measurements of cattle in 113 smallholder farms from different agro-ecological zones collected between February 2020 to January 2021 i.e., five LW measurements at months 0, 3, 6, 9, 12, live weight change for different periods, body condition scoring and physiological status referred here as "Activity data". The animal performance data together with feed quality data were used to predict the energy requirements of the animals. The animals were grouped by age and sex; adult females (>3 years), adult males (intact and castrates) (> 3 years), heifers (1-3 years), young Males (1-3years), and calves (both sexes, <1year). Estimation of daily methane production (DMP) conducted by programming the equations for ‘CSIRO’ and IPCC Tier 2 methods in Microsoft Excel. The estimations for individuals were made on a seasonal basis. The weighted average of seasonal DMPs was multiplied by 365 to obtain the annual emission factor of enteric methane production. Feed basket and digestibility calculated_NorthShewa_Ethiopia_2020 to 2021contain information on feedstuffs available and their contribution to feed baskets per agroecological zones in North Shewa. It also shows the average dry matter digestibility for each season. Milk quality data North Shewa_Ethiopia_2020 to 2021 contains information on seasonal milk quality of milk analyzed on pooled milk samples at the household level. Milk yield data North Shewa_Ethiopia_2010 to 2021 contains information on the daily milk yield of lactating cows recorded by farmers on a daily basis. Supplementary material North Shewa Ethiopia contains results in tabular form and figures to support the justification of findings. Table S1: Seasonal mean live weights change (LWC, g/day) of different classes of cattle: (females, males (intact and castrates), heifers, young males, and calves) from two agro-ecological zones (AEZ) of North Shewa zone, Ethiopia; Table S2: Net energy requirement (MJ/head/day) of different classes of cattle from IPCC Tier 2 methodology in the North Shewa zone, Ethiopia; Table S3: Maintenance energy requirement (MJ/head/day) of the different classes of cattle from ‘CSIRO’ Tier 2 methodology in the North Shewa zone, Ethiopia; Figure S1-S6: Plot of live weight versus emission factors for different cattle sub-categories for ‘CSIRO’ and IPCC Tier 2 methodologies.